The Molecular Mechanism Underlying Continuous Exercise Training-Induced Adaptive Changes of Lipolysis in White Adipose Cells - Junetsu Ogasawara; Tetsuya Izawa; Tomonobu Sakurai; Takuya Sakurai; Ken Shirato; Yoshinaga Ishibashi; Hitoshi Ishida; Hideki Ohno; Takako Kizaki (Hindawi Limited, 2015)
Physical exercise accelerates the mobilization of free fatty acids from white adipocytes to provide fuel for energy. This happens in several tissues and helps to regulate a whole-body state of metabolism. Under these conditions, the hydrolysis of triacylglycerol (TG) that is found in white adipocytes is known to be augmented via the activation of these lipolytic events, which is referred to as the "lipolytic cascade." Indeed, evidence has shown that the lipolytic responses in white adipocytes are upregulated by continuous exercise training (ET) through the adaptive changes in molecules that constitute the lipolytic cascade. During the past few decades, many lipolysis-related molecules have been identified. Of note, the discovery of a new lipase, known as adipose triglyceride lipase, has redefined the existing concepts of the hormone-sensitive lipase-dependent hydrolysis of TG in white adipocytes. This review outlines the alterations in the lipolytic molecules of white adipocytes that result from ET, which includes the molecular regulation of TG lipases through the lipolytic cascade.